Norovirus in children under 2 years of age: an epidemiological study in Panama during the COVID-19 pandemic - Rodrigo DeAntonio; Morgan Hess-Holtz; Leyda Abrego; Leyda Abrego; Zeuz Capitan-Barrios; Leyla Hernandez Donoso; Tirza De León; Tirza De León; Xavier Sáez Llorens; Xavier Sáez Llorens; Brechla Moreno; John Gerard Weil (Frontiers Media S.A., 2024)
IntroductionNorovirus infection is a common cause of acute gastroenteritis (AGE). Surveillance activities are important to aid investigation into effective norovirus control strategies, including vaccination. Here, we report ancillary findings related to the incidence, prevalence, and etiology of AGE caused by norovirus in Panama after adjustment of study methodology to comply with national coronavirus disease 2019 (COVID-19) mandates.MethodsIn January 2020, children aged <2 years began enrolling into an epidemiological study in Panama to estimate the burden of norovirus in preparation for evaluating upcoming prevention strategies. This included an observational, longitudinal, community-based AGE surveillance study and a hospital-based AGE surveillance study. For the longitudinal study, healthy children aged 5-18 months were enrolled from January 6 through March 23, 2020, with a follow-up of approximately 6 months. The last participant was contacted on September 23, 2020. For the hospital-based study, starting on January 21, 2020, children aged <2 years who were admitted to the Hospital del Niño Dr. José Renán Esquivel in Panama City due to AGE were evaluated. The last sample was collected on September 29, 2020. Collected stool samples were tested for norovirus as well as astrovirus, sapovirus, and various enteropathogens. Unfortunately, this study was disrupted by the subsequent implementation of disease transmission control procedures for the COVID-19 pandemic, and the study methodology was revised to comply with COVID-19 mandates.ResultsIn the longitudinal surveillance cohort [N = 400 (Chiriquí, n = 239; Panama, n = 161)], a total of 185 AGE episodes were documented (Chiriquí, n = 85; Panama, n = 100) resulting in an overall AGE incidence of 11.6 (95% CI: 9.99-13.4) episodes per 100 child-months. The norovirus-related AGE incidence was 0.3 (95% CI: 0.10-0.73) episodes per 100 child-months (5/185 AGE episodes) and the prevalence of norovirus was 4.6% (13/282 stool samples collected). In the hospital-based surveillance cohort, at least one pathogen was detected in 50% of samples (44/88 stool samples collected) and norovirus prevalence was 6.8% (6/88 stool samples collected).DiscussionThis report demonstrates how the occurrence of the COVID-19 pandemic hindered the conduct of clinical trials. However, this also created unique research opportunities to investigate the potential impact of pandemic control measures on the etiology of infectious diarrheal disease.